Ethylene vinyl acetate based radiation grafted hydrophilic matrices: Process parameter standardization, grafting kinetics and characterization. (August 2016) - Chaudhari, C.V.; Mondal, R.K.; Dubey, K.A.; Grover, V.; Panicker, L.; Bhardwaj, Y.K.; Varshney, L.
Abstract: A transparent, elastomeric, grafted matrix for several potential applications was synthesized by single-step simultaneous radiation grafting of methacrylic acid onto ethylene vinyl acetate (EVA). CuSO4 was found to be the most suitable homo-polymerization inhibitor among different inhibitors tried. The grafting kinetics was found to be a strong function of dose rate (D) and monomer content (M) and an equation relating grafting rate Rg =Kg [M] 1.13 D 0.23 was deduced. Crystallinity of the grafted matrices as assessed from XRD and DSC measurements indicated decrease in crystalline content with increase in grafting yield, suggesting crystalline domain of EVA get disrupted on grafting. Elastic modulus increased linearly with the increase in grafting yield, though elongation at break decreased precipitously from 900% to 30% at even 9% grafting. Thermo-gravimetric analysis showed three step weight loss of the grafted EVA matrix. The grafting of MAA resulted in increase in surface energy mainly due to enhanced polar component. Highlights: Modification of EVA elastomer into polar, hydrophilic grafted co-polymer. Easy control over properties through different extent of grafting. Mechanical properties changed from flexible polymer to rigid brittle polymer with increase in grafting extent of GMA. Grafting resulted in increase in polar component of surface energy.